Current-voltage temperature characteristics of Au/n-Ge (1 0 0) Schottky diodes - Chawanda, Albert; Mtangi, Wilbert; Auret, F.D.; Nel, Jackie M.; Nyamhere, Cloud; Diale, M. (Elsevier, 2021)
The variation in electrical characteristics of Au/n-Ge (1 0 0) Schottky contacts have been systematically investigated as a function of temperature using current–voltage (I−V) measurements in the temperature range 140–300 K. The I–V characteristics of the diodes indicate very strong temperature dependence. While the ideality factor n decreases, the zero-bias Schottky barrier height (SBH) (ΦB) increases with the increasing temperature. The I–V characteristics are analyzed using the thermionic emission (TE) model and the assumption of a Gaussian distribution of the barrier heights due to barrier inhomogeneities at the metal–semiconductor interface. The zero-bias barrier height ΦB vs. 1/2 kT plot has been used to show the evidence of a Gaussian distribution of barrier heights and values of ΦB=0.615 eV and standard deviation σs0=0.0858 eV for the mean barrier height and zero-bias standard deviation have been obtained from this plot, respectively. The Richardson constant and the mean barrier height from the modified Richardson plot were obtained as 1.37 A cm−2 K−2 and 0.639 eV, respectively. This Richardson constant is much smaller than the reported of 50 A cm−2 K−2. This may be due to greater inhomogeneities at the interface.